Factors Influencing Labor Allocation in Rubber Plantations in Muaro Jambi Regency - Nasution, Siti Sarah Almuizzah; Tinaprilla, Netti; Kusnadi, Nunung (Jurnal Manajemen dan Agribisnis, 2024)
Background: Production and the number of smallholder rubber farmers in Muaro Jambi Regency have decreased over the past ten years. The decrease in production and the number of rubber farmers are believed to be caused by a decrease in the labor allocation in rubber plantations. Rubber farmers now focus on more than just one commodity, and farmers have diversified their income resources, such as oil palm plantations and off-farm work. As a result, household economic decisions will be related to labor allocation. Purpose: This study aims to analyze the labor allocation in rubber farmer households and identify the factors influencing labor allocation in rubber plantations in the Muaro Jambi Regency.Design/methodology/approach: This research used primary data from one hundred rubber households using a multistage random sampling method. The estimation was done in two steps: in the first step, shadow wages were estimated using the production function to get the value marginal product of labor, and in the second step, the instrumental variable method was used to determine the factors influencing labor allocation in rubber plantations. Findings/Results: The estimation shows that shadow wages, oil palm labor allocation, and non-rubber income significantly influence rubber labor allocation. This result indicates that the existence of oil palm plantations does not cause a decrease in rubber labor allocation, and shadow wages can be a determining factor in labor allocation. Originality/value (State of the art): This study focuses on how rubber farmer households allocate their labor across rubber plantations, other farms, and off-farm work in the context of the presence of other commodities, particularly oil palm, which is developing alongside rubber in the research area. The results show how farmers make decisions regarding their rubber plantations, switch to oil palm, or do off-farm work, which is the reason why they began reducing labor allocation to their rubber farms. Keywords: labor allocation, household economics, shadow wages, instrumental variable, rubber plantations